ANALISIS REPRESENTASI KOMUNIKASI INTRAPERSORNAL PADA ISU SOSIAL BEAUTY STANDARD DALAM VIDEO MUSIK 'TUTUR BATIN' KARYA YURA YUNITA - Putri Rahma Safhira (2023)
The music video of Tutur Batin was uploaded on March 7, 2022 through the YouTube platform. The lyrics were written directly by Yura Yunita and her husband, Donne Maula. This study aims to discuss an intrapersonal representation of communication in semiotically analyzed Inner Speech music videos using Roland Bates' semiotics theory, and to use the theory of beauty myths as an introduction to analyzing beauty standards. In addition to the theory of message design logic as an introduction to analyzing forms of intrapersonal communication. The result of this study is that women engage in intrapersonal communication due to limited movement space when experiencing social issues of beauty standard professional beauty qualification, culture, stigma of society related to beauty ideal in Indonesia, It also holds a sense of self-confidence because it does not fit into the ideal body shape of Indonesian culture, the sex side of the body shape that does not conform to social construction standards, and the deformed body shape. It is illustrated in three theories in descriptive semiotic analysis. Key Word: Representasion, Intrapersornal Communication, Beauty Standard, Semiotic Roland Barthes